1983
DOI: 10.1007/bf00113980
|View full text |Cite
|
Sign up to set email alerts
|

Atmospheric chemistry of carbon disulphide

Abstract: The oxidation of carbon disulphide has been studied under conditions which are likely to pertain in the atmosphere. The quantum yield for direct photo-oxidation of CS~ in air at 1 arm pressure, using near UV radiation was 0.012, with OCS as a major product. The rate coefficient (k 1) for the reaction of OH with CS2, was determined from measurements of OCS formation in the near UV photolysis of HONO-CS2-O2-N~ mixtures, kl was dependent on oxygen concentration rising from ~< 4 x 10 -14 cm 3 molecule -1 s -t at O… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
26
1

Year Published

1985
1985
2018
2018

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 60 publications
(28 citation statements)
references
References 49 publications
1
26
1
Order By: Relevance
“…However, the value determined by Cox and Sheppard (1980) for OH + CHaSH using a relative method in air is approximately a factor of 3 higher than that obtained using an absolute method. A possible explanation of this discrepancy could be that the rate of reaction of OH with CHaSH is dependent upon the partial pressure of 02 present in the system as has recently been demonstrated for OH + CS2 (Jones et al, 1982;Barnes et al, 1983;Jones et al, 1983). However, Wine et al (1984a) conclude from a consideration of their experimental observations and from the product data of Hatakeyama and Akimoto (1983) that an oxygen dependence can not be the reason for the discrepancy in this particular case.…”
Section: Introductioncontrasting
confidence: 38%
“…However, the value determined by Cox and Sheppard (1980) for OH + CHaSH using a relative method in air is approximately a factor of 3 higher than that obtained using an absolute method. A possible explanation of this discrepancy could be that the rate of reaction of OH with CHaSH is dependent upon the partial pressure of 02 present in the system as has recently been demonstrated for OH + CS2 (Jones et al, 1982;Barnes et al, 1983;Jones et al, 1983). However, Wine et al (1984a) conclude from a consideration of their experimental observations and from the product data of Hatakeyama and Akimoto (1983) that an oxygen dependence can not be the reason for the discrepancy in this particular case.…”
Section: Introductioncontrasting
confidence: 38%
“…Bingemer found concentrations of DMS in the North Sea for April (first annual plankton bloom) were as high as 900 ng (S) 1-1 Air concentrations of CS2 which were determined, showed no seasonal trend and gave a mean value of 980-+ 480 ng (S)m -3. Jones et al (1983) give data for atmospheric CS2 concentrations, measured at Harwell, U.K. Two distinct sample populations were found, one with a modal value close to 80 ng (S) m-3 and the other between 530 and 800 ng (S) m-3. They suggest that the latter may indicate the presence of a strong intermittent source.…”
Section: Resultsmentioning
confidence: 99%
“…There is one other paper that investigated the photooxidation of C82 at low PCS2 [Jones et al, 1983]. They found that •OCS =0.012 and did not report a first-order dependence of d>CS2 on PCS 2.…”
Section: Experiments Investigating the Buffer Gas Dependence Of Rdcs2mentioning
confidence: 99%